Use of autochthonous lactic acid bacteria starters to ferment mango juice for promoting its probiotic roles. Issue 4 (18th May 2016) - Liao, Xue-Yi; Guo, Li-Qiong; Ye, Zhi-Wei; Qiu, Ling-Yan; Gu, Feng-Wei; Lin, Jun-Fang
ABSTRACT: Strains of Leuconostoc mesenteroides, Pediococcus pentosaceus, and Lactobacillus brevis were identified from mango fruits by partial 16S rDNA gene sequence. Based on the ability of producing mannitol and diacetyl, Leuconostoc mesenteroides MPL18 and MPL39 were selected within the lactic acid bacteria isolates, and used as mixed starters to ferment mango juice (MJ). Both the autochthonous strains grew well in fermented mango juice (FMJ) and remained viable at 9.81 log cfu mL −1 during 30 days of storage at 4°C. The content of total sugar of FMJ was lower than that of MJ, while the concentration of mannitol was higher than that of MJ, and the concentration of diacetyl was 3.29 ± 0.12 mg L −1 . Among detected organic acids including citric acid, gallic acid, lactic acid, and acetic acid, only citric acid and gallic acid were found in MJ, while all detected organic acids were found in FMJ. The concentration of lactic acid of FMJ was the highest (78.62 ± 13.66 m M ) among all detected organic acids. The DPPH radical scavenging capacity of FMJ was higher than that of MJ. Total phenolic compounds were better preserved in FMJ. The acidity and sweetness had a noticeable impact on the overall acceptance of the treated sample.